Pengembangan Model Pembelajaran Tajribi : Mengintegrasikan Fenomena Perilaku Keagamaan ke Dalam Pendidikan - Ridwan M Soleh (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2024)
A learning model is a learning concept that includes approaches, strategies, methods, techniques and tactics of learning. In this research, a tajribi learning model is developed, which means practice, application or habituation. The purpose of this research is to be a reference for teachers or educational actors in processing effective and efficient learning concepts as a whole, and not only focusing on learning methods and strategies. The method used is a literature review, by looking for previous research, then reviewing the relevant research for the development of the tajiribi learning model. efforts to integrate the phenomenon of religious behaviour into learning is a pattern worth using, which will make students more open-minded. This is the basis for the development of the Tajiribi learning model that students are accustomed to experimenting with the phenomenon of religious practices and behaviour that occurs. Hopefully, this research can be further developed with field studies to test the effectiveness of this model in schools.